Avaliação da qualidade microbiológica, físico-química e sensorial do caldo de cana-de-açúcar cultivada sob manejo orgânico e convencional - Rocha, Gisele Franco (2012)
The composition of the sugar cane juice depends on several factors, since those related inherently to the raw material or involving climate and cultural conditions. This work aimed to evaluate the influence of the conventional and organic managements of the sugar cane over the microbiological, physico-chemical and sensorial quality of the juice aiming its utilization as a beverage along two sampling periods (successive crops). Microbiological analysis of total coliforms and E. coli, aerobic mesophilic bacteria, molds and yeasts and Salmonella; physico-chemical as Pol, soluble solids, purity, pH, acidity, ash, reducing sugars, aminoacids, phenolic compounds, phosphorus, calcium, potassium and magnesium; and sensorial comparison by ordination (color and flavor) and preference tests of the juice samples were evaluated. The results of microbiological, physico-chemical and sensorial analysis did not show remarkable differences among the treatments regarding the sugar cane management, however, significant differences were observed for some parameters between the samples in successive years. The sugar cane management had no influence over the juice quality, verifying that the differences observed between the samples were probably due to the fact that the first sample (in August 2010) constitutes the first sugar cane harvest after the experiment was established (in April 2009). In the following harvest some parameters, as soluble solids, pol, purity, total reducing sugar, phosphorus, potassium and magnesium, showed significant increase in the values, indicating greater sugar cane maturity, regardless the management. The organic sugar cane juice presented satisfactory conditions, with similar quality comparing to the juice from sugar cane under conventional management. This enables the safe commercialization of this product as a beverage besides its utilization as raw material for several organic products. This is an advantageous alternative for the use of sugar cane for smallholders.